AN ENHANCED BINDING UPDATE SCHEME FOR NEXT GENERATION INTERNET PROTOCOL MOBILITY - SENTHILKUMAR MATHI; M. L. VALARMATHI (Journal of Engineering Science and Technology, 2018)
In recent years, the usage of mobile devices has become essential for people, both for business and for their daily activities. The mobile devices can get services directly from their home network and from other correspondent devices regardless of their position without using any intermediate agent. It is achieved by using mobility based Internet Protocol version 6, called as next generation internet protocol mobility. Since network mobility uses open air interface as a communication medium, it is possible for many security threats and attacks that might attempt to get unauthorized access from the participating entities. Consequently, the protection of network mobility from threats is one of the most demanding tasks as it must be considered without increasing the complexity while enhancing security. Hence, the paper proposes an enhanced location update scheme by incorporating the optimal asymmetric encryption method based on the random oracle model for providing security and efficiency. It emphasizes the security goals such as authentication, integrity, and confidentiality from the security analysis. In addition, it addresses the attack prevention analysis for the attacks such as rerun, man-in-the-middle and false location update. The proposed scheme is simulated and verified for security properties using a security validation tool - Automated Validation of Internet Security Protocols and Applications. Finally, the simulation studies show that the latency of the proposed scheme is reduced significantly when compared the other location update schemes.